2016
DOI: 10.3389/fevo.2016.00050
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Perception in Cetaceans: Part II—Promising Experimental Approaches to Study Chemoreception in Dolphins

Abstract: Chemosensory perception in cetaceans remains an intriguing issue as morphological, neuroanatomical and genetic studies draw unclear conclusions, while behavioral data suggest that dolphins may use it for food selection or socio-sexual interactions. Experimental approaches have been scarce due to the practical difficulties of testing chemoreception in wild dolphins. Go/no-go tasks are one elegant way to investigate discrimination abilities; however, they require to train the animals, thus preventing spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…A recent study demonstrated that bottlenose dolphins are capable of perceiving the odor of a dead fish in air at a distance of 2.5 m, and discriminate between fish and nonfish flavors (Kremers et al . ). Small fungiform papillae that may be associated with taste buds were recently documented on the dorsal surface of a gray whale calf tongue (Kienle et al .…”
Section: Brief Descriptions Of Cetacean Sensory Systems As Related Tomentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study demonstrated that bottlenose dolphins are capable of perceiving the odor of a dead fish in air at a distance of 2.5 m, and discriminate between fish and nonfish flavors (Kremers et al . ). Small fungiform papillae that may be associated with taste buds were recently documented on the dorsal surface of a gray whale calf tongue (Kienle et al .…”
Section: Brief Descriptions Of Cetacean Sensory Systems As Related Tomentioning
confidence: 97%
“…These indications of chemoreception ability suggest that individual cetaceans may use olfaction and gustation cues to localize and discriminate prey (Kremers et al . ), or potentially sense salinity levels to evaluate local oceanographic conditions (see Oceanographic stimuli). In the dolphin scale‐of‐senses schematic (Fig.…”
Section: Brief Descriptions Of Cetacean Sensory Systems As Related Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Kuznetzov (1990) proposed the term "quasi-olfaction" to describe the chemical sense in dolphins that combines characteristics of both gustation and olfaction. Recent behavioral studies suggest that dolphins are able to detect airborne odors and discriminate between different flavors (Kremers et al, 2016).…”
Section: Behavioral Data On Gustationmentioning
confidence: 99%
“…For instance, in contrast to captive dolphins, wild dolphins cannot be trained; therefore, other methods may have to be developed for the same research tasks. While chemoreception may be tested in captive dolphins by using odor sources close to the pool or ice cubes (see Kremers et al, 2016), floating dispensers (such as the ones used for chlorine tablets in swimming pools) may be adopted for wild dolphins. For olfactory studies, the substance to be tested is simply placed inside the device.…”
Section: Perspectives On Chemoreceptionmentioning
confidence: 99%